Vitamin K and The Immune System - Putri, Rachma Greta Perdana; Safitri, Rosyida Awalia; Herliyanti, Yuni (Ahmad Dahlan Medical Journal, 2022)
Vitamin K is a vitamin fat-soluble with the main function as an anticoagulant. The active form of vitamin K can be divided into two categories, namely vitamin K1 (phylloquinone) can be found in photosynthetic plants and vitamin K2 (menaquinone) comes from bacteria, source in foods we can found this in fermented foods like natto or soybean product which fermented by Bacillus natto. This literature review was conducted through searching in database like PubMed, and Elsevier using keywords like vitamin K, Immune system, and inflammation. The role of vitamin K in physiological functions is well known worldwide, such as blood coagulation, bone metabolism, and regulation of several types of enzymes. Apart from this role, vitamin K also acts as a cofactor in several plasma proteins, so this vitamin can influence immune responses. Recent studies have found vitamin K links to inflammatory diseases. Vitamin K also induced autophagy pathway. However, information regarding the role of vitamin K in the immune system is limited.